Measuring Process Innovation on Double-Flanked Conceptual Model for Knowledge Sharing on Online Learning Environment - S.M.F.D, Syed Mustapha; Biju Theruvil, Sayed; Roshayu, Mohamad (JATIT, 2017)
There are various innovation models that were discussed in the literature and the adoption is based on the organizational needs for their business contexts, vision and applications. These innovation models require effective innovation process framework to be followed. SECI Model has been chosen as knowledge creation model to facilitate innovation through knowledge sharing and creation. While literature has shown that SECI model has been applied in various fields such as management, manufacturing, education and business, very few has considered it as innovation tool for online learning environment. Knowledge creation requires community who has enculturated with knowledge sharing as part of the practices. For this purpose, Community of Practice (CoP) has been chosen as the essentialities for the prospective innovative community and consequently to make implementation of SECI model a success. Community with CoP values are postulated to provide the right organizational setting for innovation. It is suggested that both SECI Model and CoP are integrated as new a conceptual model being regarded as double flank strategy that synergizes to prepare the right community setting and to facilitate innovation through knowledge creation. Subsequently, this paper proposed the methods and approaches in measuring innovativeness in online learning environment based on the double flank conceptual model called DFCMI.